2022
DOI: 10.1007/s11858-022-01445-4
|View full text |Cite
|
Sign up to set email alerts
|

Comprehension of argumentation in mathematical text: what is the role of interest?

Abstract: This article describes the research design and findings from a use-inspired study of online text-based mathematics resources. We sought to understand whether and how existing mathematics interest, together with the learner characteristics of prior coursework in mathematics and proof scheme, influenced comprehension of mathematical argumentation and triggered interest in two types of mathematics text: (1) text featuring concrete, real-world applications (public domain) and (2) text with abstract and generalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…It showed that in cluster 1, mathematical argumentation in higher education was closely related to mathematical proof and instructional design. Understandably, mathematical argumentation and proficiency in proof can be regarded as cognitive abilities based on accessible resources, a shift that often occurs when advancing through higher education (Renninger et al, 2023;Sommerhoff et al, 2021). Furthermore, the standard arrangement of mathematical lectures at the university level highlights the importance of proofs and proving (Cardetti & LeMay, 2018;Nagel et al, 2018).…”
Section: Clusters Of Studies Analysing Mathematical Argumentationmentioning
confidence: 99%
See 2 more Smart Citations
“…It showed that in cluster 1, mathematical argumentation in higher education was closely related to mathematical proof and instructional design. Understandably, mathematical argumentation and proficiency in proof can be regarded as cognitive abilities based on accessible resources, a shift that often occurs when advancing through higher education (Renninger et al, 2023;Sommerhoff et al, 2021). Furthermore, the standard arrangement of mathematical lectures at the university level highlights the importance of proofs and proving (Cardetti & LeMay, 2018;Nagel et al, 2018).…”
Section: Clusters Of Studies Analysing Mathematical Argumentationmentioning
confidence: 99%
“…The study conducted by Renninger et al (2023) introduced the assessment of mathematical comprehension (AMC), an interactive online assessment. In this study, the AMC was used to investigate undergraduate students' comprehension of mathematical argumentation concerning specific textual features and individual learner characteristics.…”
Section: Assessment For Mathematical Argumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Other important motivational theories considered in the contributions were self-determination theory and Bandura's (2003) social-cognitive theory of self-efficacy, which were used simultaneously or separately in the contributions by Hettinger et al (2022), Rach (2022), Skilling and Stylianides (2022), and Zhang et al (2022). In other papers (Renninger et al, 2022;Seah, 2022;Skilling & Stylianides, 2022), researchers addressed Hidi and Renninger's (2006) theory of interest development, a cognitive engagement framework (Skilling & Stylianides, 2022), or a theory of well-being as value fulfilment (Tiberius, 2018) in the contribution by Seah (2022).…”
Section: Contributions To This Special Issuementioning
confidence: 99%
“…4.3 Contributions anchored in self-determination theory, interest theory, or well-being theory Renninger et al (2022) demonstrated that interest corresponds to and potentially scaffolds the comprehension of mathematical argumentation. Seah (2022) revealed that Chinese students valued perseverance for their mathematical well-being significantly more than other factors (e.g., mathematical engagement, relationships, or meaningfulness).…”
Section: Self-reportsmentioning
confidence: 99%